2021
DOI: 10.3390/rs13245030
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Forest Aboveground Biomass in Karst Areas Using Multi-Source Remote Sensing Data and the K-DBN Algorithm

Abstract: Accurate estimation of forest biomass is the basis for monitoring forest productivity and carbon sink function, which is of great significance for the formulation of forest carbon neutralization strategy and forest quality improvement measures. Taking Guizhou, a typical karst region in China, as the research area, this study used Landsat 8 OLI, Sentinel-1A, and China national forest resources continuous inventory data (NFCI) in 2015 to build a deep belief network (DBN) model for aboveground biomass (AGB) estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Topography data The local elevation data across the study area was surveyed in 2011 using a combination of Global Positioning System (GPS) and Real-Time Kinematic (RTK) techniques (Lin, 2017). The elevation data obtained from the survey were interpolated into regular grids using the Ordinary Kriging method.…”
Section: New Phytologistmentioning
confidence: 99%
“…Topography data The local elevation data across the study area was surveyed in 2011 using a combination of Global Positioning System (GPS) and Real-Time Kinematic (RTK) techniques (Lin, 2017). The elevation data obtained from the survey were interpolated into regular grids using the Ordinary Kriging method.…”
Section: New Phytologistmentioning
confidence: 99%
“…A random forest is a forest composed of numerous randomly generated trees. Each tree is random; thus, they are independent of each other and have no correlation or dependence [35]. Random forest is an enhanced classifier (regressor) constructed of multiple decision trees; when new data enters the random forest, all decision trees will generate classification or prediction results, and the random forest will take the mode or average of these results as the output of the data [36].…”
Section: Random Forestmentioning
confidence: 99%
“…Studies have shown that non-parametric models can effectively estimate vegetation parameters. However, for forest ecosystems, the estimation accuracy of general nonparametric models is still limited [35]. Additionally, random forest has strong anti-noise ability and can effectively deal with high-dimensional data, which has superior accuracy and robustness for vegetation parameter estimation such as leaf area index (LAI) and growing stem volume (GSV) [53].…”
Section: Effect Of Model Selection and Optimization On Estimation Acc...mentioning
confidence: 99%
“…As a crucial quantitative and qualitative indicator of forest ecosystems, forest biomass holds great importance in swiftly acquiring information on the quantity of biomass within forests [1,2]. Nevertheless, traditional remote sensing methods for estimating forest biomass suffer from disadvantages, such as low efficiency, high cost, and ecological damage.…”
Section: Introductionmentioning
confidence: 99%